Review of the genus Zelleria Stainton (Lepidoptera, Yponomeutidae, Yponomeutinae) in East Asia, with description of a new species - Na, Sol-Moon; Ponomarenko, Margarita G.; Bae, Yang-Seop (Zootaxa, 2019)
Zelleria Stainton, 1849 from the East Asia is reviewed. Zelleria asiatica Na, Bae & Ponomarenko, sp. nov. is described from Korea and Russia. Three species are redescribed and provided with a key to species, illustrations of adult, male and female genitalia, diagnoses, and descriptions. Z. japonicella Moriuti, 1977 is reported from Korea for the first time.